Analisis Kinerja Puskesmas Dengan Menggunakan Pendekatan Balanced Scorecard - Yulianti, Sri; Sualeman, Sualeman; Noor, Iqbal (Universitas Muhammadiyah Metro, 2023)
This study aims to measure the performance of Sagaranten Health Center using a Balanced approach. This study used descriptive qualitative method. Data collection by observation, interviews, questionnaires, and documentation. The analytical technique used in this study is descriptive analysis used to descriptive the data that has been collected. Data description is carried out by measuring each performance from the perspectives contained in the Balanced Scorecard, namely financial perspective, customer perspective, internal business process perspective, growth and learning perspective. The results of this study show that Puskesmas Sagranten has a satisfactory performance both in aspects of finance, customers, internal business processes, growth and learning. Although the puskesmas has achieved adequate performance, there is still room for improvement. Such as improving service quality and developing human resources.